From Tamajaght to French... To translate is to betray, but how far? - (:unkn) unknown (My University, 2022)
This paper discusses the problems and challenges of translating into French the work of a Tuareg poet, Hawad, who writes in his language, Tamajaght (Amazigh linguistic family), notated in the Tifinagh alphabet, here vocalised . Several questions are examined concerning the fact of writing in his language for an African author; the vocalisation of the consonantic alphabet of Tifinagh by the Tuaregs in the 1970s; the practical consequences of the status of minored languages on translation and translation tools; the choices made when moving from one language to another in the poetic register; neologisms...
Keywords: African Research